Codon Usage is Influenced by Compositional Constraints in Genes Associated with Dementia - Taha Alqahtani; Rekha Khandia; Nidhi Puranik; Ali M. Alqahtani; Yahia Alghazwani; Saad Ali Alshehri; Kumarappan Chidambaram; Mohammad Amjad Kamal; Mohammad Amjad Kamal; Mohammad Amjad Kamal; Mohammad Amjad Kamal (Frontiers in Genetics)
Dementia is a clinical syndrome characterized by progressive cognitive decline, and the symptoms could be gradual, persistent, and progressive. In the present study, we investigated 47 genes that have been linked to dementia. Compositional, selectional, and mutational forces were seen to be involved. Nucleotide components that influenced A- and GC-affected codon usages bias at all three codon positions. The influence of these two compositional constraints on codon usage bias (CUB) was positive for nucleotide A and negative for GC. Nucleotide A also experienced the highest mutational force, and GC-ending codons were preferred over AT-ending codons. A high bias toward GC-ending codons enhances the gene expression level, evidenced by the positive association between CAI- and GC-ending codons. Unusual behavior of the TTG codon showing an inverse relationship with the GC-ending codon and negative influence of gene expression, behavior contrary to all other GC-ending codons, shows an operative selectional force. Furthermore, parity analysis, higher translational selection value, preference of GC-ending codons over AT-ending codons, and association of gene length with gene expression refer to the dominant role of selection pressure with compositional constraint and mutational force-shaping codon usage.